Lifetime and baseline alcohol intakes and risk of pancreatic cancer in the European Prospective Investigation into Cancer and Nutrition study. Issue 4 (30th March 2018) - Naudin, Sabine; Li, Kuanrong; Jaouen, Tristan; Assi, Nada; Kyrø, Cecilie; Tjønneland, Anne; Overvad, Kim; Boutron‐Ruault, Marie‐Christine; Rebours, Vinciane; Védié, Anne‐Laure; Boeing, Heiner; Kaaks, Rudolf; et al.
Abstract : Recent evidence suggested a weak relationship between alcohol consumption and pancreatic cancer (PC) risk. In our study, the association between lifetime and baseline alcohol intakes and the risk of PC was evaluated, including the type of alcoholic beverages and potential interaction with smoking. Within the European Prospective Investigation into Cancer and Nutrition (EPIC) study, 1, 283 incident PC (57% women) were diagnosed from 476, 106 cancer‐free participants, followed up for 14 years. Amounts of lifetime and baseline alcohol were estimated through lifestyle and dietary questionnaires, respectively. Cox proportional hazard models with age as primary time variable were used to estimate PC hazard ratios (HR) and their 95% confidence interval (CI). Alcohol intake was positively associated with PC risk in men. Associations were mainly driven by extreme alcohol levels, with HRs comparing heavy drinkers (>60 g/day) to the reference category (0.1–4.9 g/day) equal to 1.77 (95% CI: 1.06, 2.95) and 1.63 (95% CI: 1.16, 2.29) for lifetime and baseline alcohol, respectively. Baseline alcohol intakes from beer (>40 g/day) and spirits/liquors (>10 g/day) showed HRs equal to 1.58 (95% CI: 1.07, 2.34) and 1.41 (95% CI: 1.03, 1.94), respectively, compared to the reference category (0.1–2.9 g/day). In women, HR estimates did not reach statistically significance. The alcohol and PC risk association was not modified by smoking status. Findings from a large prospective study suggest that baseline and lifetime alcohol intakes were positively associated with PC risk, with more apparent risk estimates for beer and spirits/liquors than wine intake. Abstract : What's new? Pancreatic cancer (PC) has been associated with alcohol consumption but studies are inconsistent and hampered by low numbers of incident events. Here, the authors studied more than 1000 PC cases and found that baseline and lifetime alcohol intakes were positively related to PC, with stronger risks for beer and spirit than wine intake. Associations were not modulated by smoking habits, underscoring the role of alcohol as a potential carcinogen for PC.